Meningkatkan Hasil Belajar IPA Melalui Model Pembelajaran Example Non Example - Sinaga, Apriani (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The purpose of this study was to determine the improvement of the quality and cognitive learning outcomes of students in the 2nd semester science subjects of Class VIII-B Gunungsitoli Middle School 4 2015/2016 Learning Year through the application of example non example learning model. This research was applied in Gunungsitoli Middle School 4 of 2015/2016 Learning Year. Subjects in this study were Class VIII-B students with a total of 17 people, and the object in this study was the application of example non example learning model. Data collection techniques use tests, observations, questionnaires, and interviews. Based on the results of research on improving science learning outcomes through cooperative learning model type example non example in Gunungsitoli Middle School 4 in cycle I with the number of students who complete students from 17 students with an average score of 63.00, while the learning outcomes of cycle II with the number of students complete 14 students with an average score of 78.00. The results of observations of students' activities in the first cycle obtained a percentage of 56.25% in the unfavorable category, while the second cycle of the student activity category increased to 81.25% in the good category. Keyword: example non example Abstrak: Tujuan dari penelitian ini untuk mengetahui peningkatan kualitas dan hasil belajar kognitif siswa pada mata pelajaran IPA semester 2 Kelas VIII-B SMP Negeri 4 Gunungsitoli Tahun Pembelajaran 2015/2016 melalui penerapan model pembelajaran example non example. Penelitian ini diterapkan di SMP Negeri 4 Gunungsitoli Tahun Pembelajaran 2015/2016. Subjek dalam penelitian ini adalah siswa Kelas VIII-B dengan jumlah 17 orang, dan objek dalam penelitian ini adalah penerapan model pembelajaran example non example. Teknik pengumpulan data menggunakan tes, observasi, angket, dan wawancara. Berdasarkan hasil penelitian peningkatan hasil belajar IPA melalui model pembelajaran kooperatif tipe example non example di SMP Negeri 4 Gunungsitoli pada siklus I dengan jumlah siswa yang tuntas siswa dari 17 siswa dengan nilai rata-rata 63,00, sedangkan hasil belajar siklus II dengan jumlah siswa yang tuntas 14 siswa dengan nilai rata-rata 78,00. Hasil observasi aktivitas siswa siklus I diperoleh persentasi 56,25% kategori kurang baik, sedangkan siklus II kategori aktivitas siswa meningkat menjadi 81,25% kategori baik. Kata kunci: example non example